The rise of BRICS: implications for global agrarian transformation - McKay, Ben M.; Hall, Ruth; Liu, Juan (Third World Thematics: A TWQ Journal, 2016)
This article introduces this collection, which focuses on the economic and political rise of the BRICS countries (Brazil, Russia, India, China, and South Africa) and its implications for global agrarian transformation. These emerging economies are undergoing profound changes as key sites of the production, circulation, and consumption of agricultural commodities; hosts to abundant cheap labour and natural resources; and home to growing numbers of both poor but also, increasingly, affluent consumers. Separately and together these countries are shaping international development agendas both as partners in, and potential alternatives to, the development paradigms promoted by the established hubs of global capital in the North Atlantic and by dominant international financial institutions. Collectively, the findings show the significance of BRICS countries in reshaping agro-food systems at the national and regional level, and their global significance. As they export their own farming and production systems across different contexts, though, the outcomes are contingent and success is not assured. At the same time, BRICS may represent a continuation rather than an alternative to the development paradigms of the Global North.